HIGHER ORDER THINKING QUESTIONS IN ENGLISH TEST OF SENIOR HIGH SCHOOL - Oktaviana Mayang Dewi; Semi Sukarni (p-ISSN 2356-0576, 2020)
Abstract: The objectives of this research are to identify the composition of the cognitive levels of higher order thinking questions and the comparison between LOTS and HOTS questions contained in the final semester test.  This is a qualitative study which employed documentation as its data collection technique. The data were sourced from the final semester test of English subject comprising 55 test items. The revised Bloom’s taxonomy was used to analyzed the test items which covers remembering, understanding, applying, analyzing, evaluating and creating. The finding shows that  the composition of Bloom’s taxonomy of cognitive levels covered 11 items (20%) of remembering (C1), 35 items (63.1%) of understanding (C2), 3 (5.4 %) items of applying (C3), 2 items (3.4%) of  analyzing (C4), 3 items (5.4 %) of  evaluating (C5),  and 1 (1.9%) of creating (C6). The comparison between LOTS and HOTS was 49 items (89%) of LOTS  and 6  items (10.9%) of HOTS. It can be stated that the test was still be dominated by lower order thinking questions.   Keywords: Final semester test, HOT, question, revised Bloom’s taxonomy.